ANALISIS PROFITABILITAS KERIPIK SINGKONG PADA INDUSTRI RUMAH TANGGA PASUNDAN DI KOTA PALU - Patoki, Alto Kristian; Effendy, Effendy (AGROTEKBIS, 2017)
The study aims to determine the amount of revenue and profitability of the business value of cassava chips in the industry